Sleep medicine in pneumology - Randerath, W J (Deutsche medizinische Wochenschrift (1946), 2011)
Diagnosis and treatment of sleep related breathing disorders have become an essential challenge of internal medicine. They are highly important clinically because of the impairment of daytime performance, attention and concentration with elevated risk of accidents in workplace and traffic and because of their consequences on cardiovascular and metabolic disorders. The obstructive sleep apnoea syndrome (OSAS) has proven to be one of the most important risk factors for arteriosclerosis, especially in the cerebral vessels. OSAS induces arterial hypertention and increases mortality due to cardiovascular diseases. Sleep related breathing disorders induce hyperglycemia and dyslipidemia. OSAS and the metabolic syndrome increase the cardiovascular risk additively. Moreover, cardiac disorders, such as arterial hypertention, heart failure and arterial fibrillation, can induce central breathing disturbances. This impairs the prognosis of affected patients substantially. Atypical symptoms of obstructive sleep apnoea (daytime sleepiness, snoring, witnessed apnoea) are often absent in these patients. In contrast patients often suffer from fatigue, reduced daytime performance, and depression which is a major challenge to diagnosis. This review presents new data on these aspects. Moreover, the association of sleep apnoea and pulmonary embolism and the question of optimal sleep duration are addressed.